The person in dementia : a study in nursing home care in the US - McLean, Athena, 1948- (Broadview ethnographies & case studies., 2007)
Winner of the Society for Medical Anthropology's 2009 New Millennium Award Imagine yourself in advanced age, forced to depend on others for all your basic needs. What would you want to retain of your personal life? This question is at the heart of a set of case studies that examine the lives of nursing home residents who were diagnosed with senile dementia. Based on two years of intensive comparative ethnographic study in a nursing home in a Northeastern American city, The Person in Dementia dramatically contrasts the outcomes of two approaches to dementia care for elders with severely disturbed behaviors: a task-oriented approach based on a biomedical view of disease progression and a flexible person-sustaining approach focusing on individual needs and communication. By emphasizing "personhood," which looks beyond physical and reasoning abilities to a person's will and relationship with others, McLean conceptualizes dementia care as a moral enterprise. She encourages innovative and compassionate elder care and accountability across the spectrum from direct care-givers to nursing home owners to those at the highest levels of government. McLean also offers a fine-tuned analysis of how relations among direct care-giving, professional, and administrative staff within a facility can dramatically affect the quality of dementia care. The book includes policy recommendations that are geared to long-term care administrators and policy-makers as well as to caregivers, families, and elders with dementia